TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN PADA PERUSAHAAN BADAN USAHA MILIK NEGARA PERTAMINA HULU SANGA – SANGA BERDASARKAN UNDANG – UNDANG NOMOR 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS - Dani, A. Syahrul Muhamad (Universitas 17 Agustus 1945 Samarinda, 2022)
AbstracCorporate Social Responsibility (CSR) or which in Law Number 40 of 2007 concerning Limited Liability Companies is called Social and Environmental Responsibility (TJSL). Social and Environmental Responsibility is an obligation activity for every company to implement it as ordered by Law Number 40 of 2007 concerning Limited Liability Companies. PT Pertamina Hulu Sanga-Sanga with an office in Muara Badak District. PT Pertamina Hulu Sanga is a subsidiary of PT Pertamina Hulu Indonesia which is united as a State-Owned Enterprise (BUMN), soit should be a benchmark for other companies in terms of moving. This type of research in writing this thesis uses an empirical and normative approach, in which in this case the author goes into the field to see firsthand the objective conditions on the issues raised and consider them based on existing laws. The results of the research show that the implementation of the Social and Environmental Responsibility of PT Pertamina Hulu Sanga-Sanga still inherits the concepts and methods from its predecessor company, Virginia Indonesia Company (VICO). Sanctions against companies that do not carry out their Social and Environmental Responsibility obligations are still very weak, as regulated in Law Number 25 of2007 concerning Investment, there are only administrative sanctions for companies that do not carry out them, and other laws and regulations do not regulate related to sanctions, in this case it can put a rogue company in a safe position even though it does not carry out its Social and Environmental Responsibility obligations. In fact, if we refer to Law Number 40 of 2007 concerning Limited Liability Companies, there is a noble goal of implementing Social and Environmental Responsibility, namely to realize sustainable economic development. Keywirds : Social and Environmental Responsibility, Implementation, Sanctions